2008
DOI: 10.3174/ajnr.a1261
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body CT Trauma Imaging with Adapted and Optimized CT Angiography of the Craniocervical Vessels: Do We Need an Extra Screening Examination?

Abstract: BACKGROUND AND PURPOSE: Blunt carotid and vertebral artery injury (BCVI) is rare but potentially devastating. The objective of our study was to prospectively evaluate the usefulness of a dedicated and optimized CT angiography (CTA) protocol of the craniocervical vessels as part of a whole-body CT work-up of patients with multiple trauma in a population of patients with blunt trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…However, patients with low-impact MOIs would merit multidetector CT angiographic evaluation only if there is a fracture reaching the expected location of an arterial structure or a high index of clinical suspicion. Among the different unenhanced CT fi ndings, we found the risk of arterial injury to be highest in patients with cervical interfacetal subluxations/ dislocations (44.4%), and fracture lines that reached either the foramen transversarium (22.8%) or the ICA canal (18.5%), which are similar to the results of prior studies ( 7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, for cervical spine fractures reaching the foramen transversarium, we found that the risk for vertebral artery injury was signifi cantly higher in the lower cervical spine (36.3%) than in the upper cervical spine (12.3%).…”
Section: Neuroradiology: Ct Angiography and Acute Craniocervical Traumasupporting
confidence: 88%
See 3 more Smart Citations
“…However, patients with low-impact MOIs would merit multidetector CT angiographic evaluation only if there is a fracture reaching the expected location of an arterial structure or a high index of clinical suspicion. Among the different unenhanced CT fi ndings, we found the risk of arterial injury to be highest in patients with cervical interfacetal subluxations/ dislocations (44.4%), and fracture lines that reached either the foramen transversarium (22.8%) or the ICA canal (18.5%), which are similar to the results of prior studies ( 7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, for cervical spine fractures reaching the foramen transversarium, we found that the risk for vertebral artery injury was signifi cantly higher in the lower cervical spine (36.3%) than in the upper cervical spine (12.3%).…”
Section: Neuroradiology: Ct Angiography and Acute Craniocervical Traumasupporting
confidence: 88%
“…However, for cervical spine fractures reaching the foramen transversarium, we found that the risk for vertebral artery injury was signifi cantly higher in the lower cervical spine (36.3%) than in the upper cervical spine (12.3%). These fi ndings are similar to some of the prior multidetector CT angiographic studies that have reported specifi c cervical spine fracture levels for patients with vertebral artery injury ( 11,14 ), although Utter et al ( 18 ) and other catheter angiographic studies ( 6,16,17 ) have reported higher yields in patients with fractures of the upper cervical spine. Notably, we found the risk of vertebral artery injury to be particularly high in patients with fractures of the C5 vertebral body reaching the foramen transversarium (38.5%) and the risk of ICA injury to be highest in CT angiographic studies, which have reported yields ranging from 1.2% to 28.4% ( 7,(9)(10)(11)(12)(13)(14)(15)18 ).…”
Section: Neuroradiology: Ct Angiography and Acute Craniocervical Traumasupporting
confidence: 86%
See 2 more Smart Citations
“…The reported incidence of these has increased owing to the extensive application of screening imagistic methods, such as ultrasound, CT angiography and digital subtraction angiography (DSA). (1,2) These types of injuries are associated with morbidity and mortality rates ranging between 23 to 28%, and 48-58% of survivors have significant neurological complications. (3,4) Blunt cerebrovascular injuries differ in many ways from spontaneous carotid, and vertebral artery dissections and frequently are associated with other traumatic lesions.…”
Section: Introductionmentioning
confidence: 99%